Pengaruh Reward dan Punishment Terhadap Motivasi Kerja pada PT. Bank SulutGo Cabang Suwawa - Reynaldi Trifando Alaina; Muchtar Ahmad; Andi Yuniar Mendo (Economic Reviews Journal, 2025)
This study aims toexamine the effect of reward and punishment on work motivation. The study employs a quantitative approach based on statistical data. The population in the study consist of employees at PT. Bank SulutGo, Suwawa Branch, totalling 47 employees. Due to the small population size (less than 100), a total sampling method was used and all 47 employees were include as samples in study. The data analysis method used in yhis study is Multiple Linear Regression Analysis, conducted using SPSS 16 software. The result indicate that both reward and punishment have a significant partial effect on work motivation. Simultaneously, reward and punishment together account for 0,461 or 64,1% of the varoiace in work motivation, while the remaining 35,9% is affected by other variables such as the desire for survival, the desire for ownership, the desire for power, and the assurance of obtaining a better job.